The Cambridge introduction to W.B. Yeats - Holdeman, David (Cambridge University, 2013)
This introduction to one of the twentieth century's most important writers examines Yeats's poems, plays and stories in relation to biographical, literary, and historical contexts. Yeats wrote with passion and eloquence about personal disappointments, his obsession with Ireland, and the modern era's loss of faith in traditional beliefs about art, religion, empire, social class, gender and sex. His works uniquely reflect the gradual transition from Victorian aestheticism to the modernism of Pound, Eliot and Joyce. This is the first introductory study to consider his work in all genres in light of the latest biographies, new editions of his letters and manuscripts, and recent accounts by feminist and postcolonial critics. While using this introduction, students will have instant access to the world of current Yeats scholarship as well as being provided with the essential facts about his life and literary career and suggestions for further reading.